Emergence and Evolution of Novel Canine-Avian Reassortant H3N2 Influenza A Viruses in Duck in Leizhou Peninsula, China - Yao, Qiucheng; Mai, Wenhong; Lian, Yuexiao; Zhang, Mengdi; Yao, Qiang; Huang, Caiyun; Ge, Ye; Zhao, Zhihui (Frontiers in Microbiology, 2022)
Avian-to-mammal transmission and mammalian adaptation of avian influenza virus (AIV) are threats to public health and of great concern. The H3 subtype of influenza virus has low pathogenicity and is widely distributed in humans, canines, equines and avians. In 2018-2019, we isolated six H3N2 subtype influenza viruses from 329 samples acquired from ducks on the Leizhou Peninsula, China, as part of an ongoing virus surveillance program. All viruses were analyzed by whole-genome sequencing with subsequent genetic comparison and phylogenetic analysis. Phylogenetic analysis demonstrated that reassortment of these viruses has occurred among different hosts and subtypes. Some of the H3 AIV isolates have similar genes as subtypes H5 and H7 of highly pathogenic avian influenza viruses (HPAIVs). Most importantly, one strain of H3N2 virus is a novel reassortant influenza virus containing HA and PB2 segments from canine H3N2 virus. The time of most recent common ancestor (tMRCA) data indicated that this reassortant H3N2 virus might have emerged in 2011-2018. The findings suggest that the viruses studied here have undergone multiple reassortment events. Our results provide a framework for understanding the molecular basis of host-range shifts of influenza viruses and indicate that dogs are potential “mixing vessels” for influenza virus transmission.